INVISIBLE SEASIDES a new way of redeeming a utopias past and imagining its afterlife. - Blackshaw, Tony, 1960- (ROUTLEDGE, 2026)
Invisible Seasides positions the seaside as a lens for understanding lived utopia, pinned in a certain place, an immovable feature in a landscape where our hopes and fears continue to unfold. Wide-ranging in theme, it brings a double perspective, past and present, to bear on how we understand contemporary seaside experience.Presenting a magical paradox of the modern seaside, this book traces the development of a cultural phenomenon from the mid-1800s to the present day. In the process, it modifies the accepted narrative about its rise and fall, reappraising our understanding of the end of a Mass Utopia, and shining new light on the diversity of post-utopias that have emerged in its afterlife.Fusing social theory, social history, and leisure studies, its thesis adroitly envisions the diverse density of the seaside through a critical lens, making the unfamiliar familiar and vice versa, providing us with an exemplar for a different way of thinking sociologically, which will be used by scholars from a range of different subject fields to encourage fresh reflection on social continuity and change.